Acceleration of Translational Mesenchymal Stromal Cell Therapy Through Consistent Quality GMP Manufacturing - Jayaraman, Premkumar; Lim, Ryan; Ng, Jacqueline; Vemuri, Mohan C. (Frontiers in Cell and Developmental Biology, 2021)
Human mesenchymal stromal cell (hMSC) therapy has been gaining immense interest in regenerative medicine and quite recently for its immunomodulatory properties in COVID-19 treatment. Currently, the use of hMSCs for various diseases is being investigated in >900 clinical trials. Despite the huge effort, setting up consistent and robust scalable manufacturing to meet regulatory compliance across various global regions remains a nagging challenge. This is in part due to a lack of definitive consensus for quality control checkpoint assays starting from cell isolation to expansion and final release criterion of clinical grade hMSCs. In this review, we highlight the bottlenecks associated with hMSC based therapies and propose solutions for consistent GMP manufacturing of hMSCs starting from raw materials selection, closed and modular systems of manufacturing, characterization, functional testing, quality control, and safety testing for release criteria. We also discuss the standard regulatory compliances adopted by current clinical trials to broaden our view on the expectations across different jurisdictions worldwide.